Indisputably essential: The economics of dispute settlement institutions in trade agreements - Alexander Keck; Simon Schropp (World Trade Organization (WTO), 2007)
Economic theory has made considerable progress in explaining why sovereign countries cooperate in trade. Central to most theories of trade cooperation are issues of self-enforcement: The threat of reprisal by an aggrieved party maintains the initial balance of concessions and prevents opportunism. However, economic scholarship has been less coherent in explaining why countries choose to settle and enforce their trade disputes with the help of an impartial third party, a “trade court”. Typically, economists focusing on the purpose of trade agreements have assumed away the very reasons why institutions are needed, since under standard assumptions, neither defection from the rules nor disputes are expected to occur. This paper is a step towards the formulation of a coherent economic theory of dispute settlement. It challenges traditional models of enforcement (primarily concerned with acts of punishment) for being insufficient in explaining the existence of dispute settlement institutions. We perform a comprehensive analysis of the economics of dispute settlement institutions and demonstrate to what extent the literatures of trade cooperation and dispute institutions are (and should be) interlinked. On the basis of these theories, we show that dispute settlement institutions in trade agreements may assume a variety of roles, including that of an information repository and disseminator, an honest broker, an arbitrator and calculator of damages, an active information gatherer or an adjudicator.
Keywords: F02; F13; F51; F53; F55; K33; K41; K42; 330; Dispute settlement; trade; institutions; enforcement; WTO; Handelsabkommen; Internationale Schiedsgerichtsbarkeit; WTO-Regeln